Metabolic syndrome in skin tags: a hospital based observational study - Das, Subrata Kumar; Das, Saptadipa (International Journal of Research in Dermatology, 2021)
Background: The aim was to evaluate the parameters of metabolic syndrome in patients of skin tags and to investigate the possibility of an existing relationship between metabolic syndrome and skin tags. Methods: This cross-sectional observational study included 47 patients with skin tags attended Outpatient department (OPD) of Department of Dermatology at a tertiary care center during a period of 1 year. Clinical and laboratory parameters were noted in each patient. Results: This study included 47 patients with skin tags (28 males and 19 females). In the present study maximum number of patients belonged to the age group >40 years with 19 patients, followed by 30-40 years with 13 patient. In this study no. of students were 15, and no of employee were 11. Most patients had skin tags in more than one area, neck and axilla were involved in 9 patients each. In this study out of 47 patients. 11 patients had derangement of clinical and laboratory parameters of metabolic syndrome based on NCEP adult treatment panel III. Conclusions: In the present study we observed significant derangement of clinical and laboratory parameters of metabolic syndrome in patients of skin tags.